Determinants of dealer support factors in dealer-supplier relationship satisfaction / Ramli Saad … [et al.] - Saad, Ramli; Omar, Noorain; Abdullah, Mohd Zulhelmey (2015)
Dealers as the channel members play important roles for every organization because through them the products can reach smoothly to their target customers. Therefore, this paper aims to empirically examine the extent to which dealer support correlate with dealer-supplier relationship satisfaction. A sample of 150 respondents was randomly chosen in this survey which 130 respondents gave the feedback. Correlation and regression analysis are being used to determine the relationship between dealer-supplier relationship satisfaction variables (product attributes, monetary rewards, promotion support, and customer services) and dealer support. The result from hypotheses testing has shown that all independent variables have positive relationship with dealer support. The result on regression shows that customer services to dealer have the strongest positive relationship with dealer support compare to other variables. Results which obtained from the study can be useful in future for supplier to make better decision in dealing with their dealers.